1976
DOI: 10.1007/bf00219149
|View full text |Cite
|
Sign up to set email alerts
|

Arterio-venous anastomoses in rainbow trout gill filaments

Abstract: The origin of arterio-venous anastomoses, connecting the efferent filament artery (EFA) with the central venous sinus (CVS) of gill filaments can be well discerned by scanning electron microscopy in the rainbow trout. Corresponding vessels between the afferent filament artery and the CVS could not be detected with the techniques applied. AVA-specific endothelial cells are characterized by their bulky shape and their microvillous surface. The general morphology of AVA's in Salmo gairdneri is very similar to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…The haemodynamic model of Vogel et al (1973Vogel et al ( , 1976, confirmed by Girard & Payan (1976), is entirely consistent with the relative delay (T50)…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The haemodynamic model of Vogel et al (1973Vogel et al ( , 1976, confirmed by Girard & Payan (1976), is entirely consistent with the relative delay (T50)…”
Section: Resultssupporting
confidence: 64%
“…The hypothesis of Steen & Kruysse (1964) suggested that, in the eel, a by-pass shunts part of blood flowing from the heart away from the lamellar exchange system. A detailed morphological analysis in two other species: Tilapia mossambica and Salmo gairdneri suggests an alternative model of circulation (Morgan & Tovell, 1973;Dunel & Laurent, 1973;Vogel, Vogel & Kremers, 1973;Vogel, Vogel & Schlote 1974;Vogel, Vogel & Pfautsch, 1976;Dunel, 1975;Girard & Payan, 1976; E. G. Gannon & D. J. Randall, personnel communication).…”
Section: Introductionmentioning
confidence: 99%
“…Results from the present experiment suggest that such microridge functions may be more probable than their function as respiratory surfaces in 0. mossambicus. The presence of intricate microridge patterns on the secondary lamellar surfaces of rainbow trout (Hughes 1979, Kendall & Dale 1979, Olson & Fromm 1973, Vogel et al 1976 indicates that they may well have a respiratory function in this species. Fishelson (1980) noted that freshwater tilapia have fewer epithelial microridges on their gill filaments than saltwater-adapted specimens and suggested that microridge formation was a re-sult of epithelial cell shrinkage in euryhaline species in order to expose the underlying orifices of chloride cells.…”
Section: Discussionmentioning
confidence: 98%
“…The only factors one could imagine are the perfusion flow-rate and/or the unstirred layers of water on the internal and external sides of the lamellar epithelium. In the framework of cardiac flow-rate and utilizing the hemodynamic model of Vogel, Vogel and Kremers (1973) and Vogel, Vogel and Pfautsch (1976), confirmed by Girard and Payan (1976), the totality of blood leaving the heart crosses the secondary gill lamellae. Since the perfusion flow-rate was 3 ml.…”
Section: Validity Of the Techniquementioning
confidence: 99%